1. ## Math Project

Ok, I have a math project. We have to pick a month (I chose November which has 30 days) and make an equation for each of those days. These are our variables that we can use only once per equation, and we have to use each variable once per equation.

A= 1 B= -2 C= 3 D= -4

I need help creating the equations, the only numbers that I need now are: 13, 14, 16, 18, 19, 20, 27, 28, and 29.

We can only use the order of operations (Parenthesis, Exponents, Multiplication, Division, Addition and Subtraction)

EXAMPLE:

d-b+axc= 1

Thanks so much!!

2. ## Oh

Oh and the answer cannot be negative.

3. Originally Posted by susie44
Ok, I have a math project. We have to pick a month (I chose November which has 30 days) and make an equation for each of those days. These are our variables that we can use only once per equation, and we have to use each variable once per equation.

A= 1 B= -2 C= 3 D= -4

I need help creating the equations, the only numbers that I need now are: 9, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 26, 27, 28, 29, and 30.

We can only use the order of operations (Parenthesis, Exponents, Multiplication, Division, Addition and Subtraction)

EXAMPLE:

d-b+axc= 1

Thanks so much!!
You mean something like
$\displaystyle b - a - c \times d = 9$?

-Dan

4. ## yes!!

yes thank you so much! do you know anymore?

5. $\displaystyle -a+b-cd=13$
$\displaystyle -ab-cd=14$
$\displaystyle a-b-cd=15$
$\displaystyle d^{a+b+c}=16$
$\displaystyle (a-d)c-b=17$
$\displaystyle (-b-d)ac=18$
$\displaystyle (-b-d)c+a=19$
$\displaystyle (c-b)(a-d)=20$
$\displaystyle (c-d)(a-b)=21$
$\displaystyle (a-d)^{-b}-c=22$
$\displaystyle (-cd+a)(-b)=26$
$\displaystyle c^{-b}(-a-d)=27$
$\displaystyle (a-d)^{-b}+c=28$
$\displaystyle (-b)^{a-d}-c=29$
$\displaystyle (a-d)(-bc)=30$

6. Originally Posted by red_dog
$\displaystyle -a+b-cd=13$
$\displaystyle -ab-cd=14$
$\displaystyle a-b-cd=15$
$\displaystyle d^{a+b+c}=16$
$\displaystyle (a-d)c-b=17$
$\displaystyle (-b-d)ac=18$
$\displaystyle (-b-d)c+a=19$
$\displaystyle (c-b)(a-d)=20$
$\displaystyle (c-d)(a-b)=21$
$\displaystyle (a-d)^{-b}-c=22$
$\displaystyle (-cd+a)(-b)=26$
$\displaystyle c^{-b}(-a-d)=27$
$\displaystyle (a-d)^{-b}+c=28$
$\displaystyle (-b)^{a-d}-c=29$
$\displaystyle (a-d)(-bc)=30$

thanks, some of these were very helpful. but you can't change the value of the variable, meaning you can't make A into -A. thanks thouhg

7. Originally Posted by susie44
thanks, some of these were very helpful. but you can't change the value of the variable, meaning you can't make A into -A. thanks thouhg
that makes no sense. you listed "subtraction" as one of your allowed operations. so saying -A is just saying subtract A or possibly the negative of A, which we can make it work anyway

which of red_dog's answers do you have a problem with? the ones with the powers?

8. ## sorry

Originally Posted by Jhevon
that makes no sense. you listed "subtraction" as one of your allowed operations. so saying -A is just saying subtract A or possibly the negative of A, which we can make it work anyway

which of red_dog's answers do you have a problem with? the ones with the powers?

yeah i realized that after i posted the reply, im sorry. idk why but i always forget that rule and i ran back through the problems and found some more that worked
thanks

9. and yes, the ones with the powers didnt work on my calculator (its an advanced one) and then i tried it manually, but it didn't work out either. but still, some did work (even though they didnt come out to the answer he said)